2018
DOI: 10.1111/ijd.13977
|View full text |Cite|
|
Sign up to set email alerts
|

Recognition of early melanoma: a monocentric dermoscopy follow‐up study comparing de novo melanoma with nevus‐associated melanoma

Abstract: Significant differences, distinguishing NAMs from DNMs, were detected particularly when considering both baseline signs and follow-up changes. Earlier identification of NAMs and their subsequent improved histological characterization will help define the subgroup of high-risk patients, for whom comprehensive image monitoring may be beneficial.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 30 publications
(96 reference statements)
2
4
0
Order By: Relevance
“…NAMs are melanomas with greater diameter than DNM . Concerning dermoscopy, the features more commonly found are negative network (the most specific criteria according to some authors), globules, peripheral streaks, atypical network, and regression structures (white or peppering) . Atypical vascularization, asymmetrical pigment blotches, and blue‐whitish veil are less likely to appear in NAM, as it happens in our work.…”
Section: Discussionsupporting
confidence: 65%
“…NAMs are melanomas with greater diameter than DNM . Concerning dermoscopy, the features more commonly found are negative network (the most specific criteria according to some authors), globules, peripheral streaks, atypical network, and regression structures (white or peppering) . Atypical vascularization, asymmetrical pigment blotches, and blue‐whitish veil are less likely to appear in NAM, as it happens in our work.…”
Section: Discussionsupporting
confidence: 65%
“…Notably, we found that melanomas from patients who carry genetic variants protective for melanoma risk exhibit tumors with regression structures, shiny white structures, pigment network, and microerosions, which are dermoscopic features more prevalent in DNMMs and in more invasive melanomas with a worse prognosis (Alvarez Martinez et al., 2018; Deinlein et al, 2017; Silva et al., 2013). Interestingly, blue‐whitish veil has been previously associated with DNMMs (Shitara, Nascimento, et al, 2015), and shiny white structures with thicker or more invasive melanomas (De Giorgi & Carli, 2002; Deinlein et al, 2017; Ribero et al., 2016).…”
Section: Discussionmentioning
confidence: 98%
“…Melanoma is a cutaneous neoplasm originated from melanocytes, but its origin has always been a controversial subject (Bevona et al., 2003; Shitara, Tell‐Martí, et al, 2015; Thomas & Groben, 2004). Although most melanomas arise de novo, without contiguity with any pre‐existing nevus, pathology‐based studies have found that 20%–30% of melanomas arise from a pre‐existing melanocytic nevus (Alvarez Martinez et al., 2018; Cymerman et al, 2016). De novo melanomas (DNMMs) arise in a context related to a low nevus count (<50 nevi), while nevus‐associated melanomas (NAMMs) are more prevalent in patients with a high nevus count (>50 nevi; Haenssle et al., 2016).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The reported dermoscopic features of NAM compared to de novo melanoma vary across studies and are presented in Table 3 52–56 . However, only two studies included a larger number of NAMs 52,55 .…”
Section: Dermoscopic Findings Of Nam Compared To De Novo Melanomamentioning
confidence: 99%